Rice Bran Substitution to Vitabran as A Snackyfication Trend Model and Diabetes Mellitus Prevention - Handayani, Oktia Woro Kasmini; Kurnia, Arif Rahmat; Fathonah, Siti (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Snackyfication is a trend where snacks as a substitute for staple food are more efficient. On the other hand, the Diabetes Mellitus case increases, and it is related to unhealthy foods, so there is a need for healthy foods on the market. The research objective was to find which product formula would be recommended as Vitabran. Vitabran is made from rice bran, while additional ingredients are yellow sweet potato pulp, cornstarch, soy milk, flour, eggs, honey, baking powder, margarine, and oats. The formula tested consists of 2 variations of bran content (20% and 30%). The product was made of biscuits in the form of bars. The tests consisted of 1) organoleptic test 2) hedonic test. 3) proximate test and 4) Glycemic Index test. The final result of functional food substitution is a synergistic effect of the functional substances contained therein.